The Relationship Between Insufficient Sleep and Depressive Symptoms in Chinese Adolescents: A National Survey of Contributing Factors - Yan C; Zheng W; Du Y; Li Y; Wang M; Qu M (Nature and Science of Sleep, 2025)
Chuming Yan,1 Wancheng Zheng,1 Yun Du,1 Yi Li,2 Mengshu Wang,2 Miao Qu1 1Neurology Department, Xuanwu Hospital of Capital Medical University, Beijing, People’s Republic of China; 2Neurology Department, Third Affiliated Hospital, Beijing University of Chinese Medicine, Beijing, People’s Republic of ChinaCorrespondence: Miao Qu, Neurology Department, Xuanwu Hospital of Capital Medical University, Xicheng District, Beijing, 100053, People’s Republic of China, Email qumiao@xwhosp.orgPurpose: There is a lack of national studies examining the relationship between insufficient sleep and depression among Chinese adolescents, and previous research has not comprehensively considered related factors. This study aimed to investigate the prevalence of depressive symptoms in adolescents with insufficient sleep and explore the role of associated factors using a nationally representative sample in China.Patients and Methods: A pen-and-paper survey was conducted among 24147 Chinese adolescents from November 2019 to January 2020. Data on depressive symptoms, maltreatment experiences, psychological resilience, demographic information, parent–child relationships, parental marital status, and sleep duration were collected.Results: A total of 22231 valid questionnaires were analyzed. Among the respondents, 67.7% reported insufficient sleep, while 32.3% had sufficient sleep. The prevalence of depressive symptoms was 25.3% in adolescents with insufficient sleep, compared to 8.2% in those with sufficient sleep. Insufficient sleep was identified as an independent risk factor for depressive symptoms (OR = 3.058, 95% CI: 2.753– 3.396, P < 0.001). In adolescents with sufficient sleep, being female, emotional abuse, physical abuse, sexual abuse, and physical neglect were significant risk factors for depressive symptoms (P < 0.05), while higher resilience scores and a good parent–child relationship were protective factors (P < 0.05). Among adolescents with insufficient sleep, additional risk factors included higher body mass index (BMI), older age, parental divorce, and living with a single parent (P < 0.05).Conclusion: Insufficient sleep is significantly associated with depressive symptoms in Chinese adolescents. The adolescents with insufficient sleep, particularly those who are older, have a higher BMI, or come from divorced or single-parent households, require increased attention.Keywords: depressive symptoms, sleep duration, adolescent mental health, parent–child relationship